2013
DOI: 10.1071/rd12256
|View full text |Cite
|
Sign up to set email alerts
|

Successful cloning of coyotes through interspecies somatic cell nuclear transfer using domestic dog oocytes

Abstract: Interspecies somatic cell nuclear transfer (iSCNT) is an emerging assisted reproductive technology (ART) for preserving Nature's diversity. The scarcity of oocytes from some species makes utilisation of readily available oocytes inevitable. In the present study, we describe the successful cloning of coyotes (Canis latrans) through iSCNT using oocytes from domestic dogs (Canis lupus familiaris or dingo). Transfer of 320 interspecies-reconstructed embryos into 22 domestic dog recipients resulted in six pregnanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Similarly, coyote pups ( Canis latrans ) were produced using dog ( Canis lupus familiaris ) oocytes [17] and a gaur calf ( Bos gaurus ) was produced from embryos reconstructed with bovine ( Bos taurus ) oocytes [8]. Even iSCNT embryos reconstructed from mouflon ( Ovis orientalis musimon ) donor cells and sheep ( Ovis aries ) oocytes [10] developed to term.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, coyote pups ( Canis latrans ) were produced using dog ( Canis lupus familiaris ) oocytes [17] and a gaur calf ( Bos gaurus ) was produced from embryos reconstructed with bovine ( Bos taurus ) oocytes [8]. Even iSCNT embryos reconstructed from mouflon ( Ovis orientalis musimon ) donor cells and sheep ( Ovis aries ) oocytes [10] developed to term.…”
Section: Discussionmentioning
confidence: 99%
“…This technology has triumphed only when using very closely related animals, with other cases including cloning of the coyote ( Canis latrans ) using domestic dog ( Canis lupus familiaris ) cells and surrogates (Hwang et al . ), wild cat ( Felis silvestris lybica ) and sand cat ( Felis margarita ) using the domestic cat ( Felis catus ; Gómez et al . , ), and a mouflon ( Ovis orientalis musimon ), an endangered subspecies of sheep, using domestic sheep ( Ovis aries ) oocyte and surrogate following nucleus retrieval from a cell of a deceased mouflon (Loi et al .…”
Section: De‐extinction Through Artificial Reproductive Technologiesmentioning
confidence: 99%
“…Cloning by iSCNT involves the transfer of a somatic cell nucleus to the enucleated oocyte of a different species or subspecies, and would be the method used for de-extinction due to the obvious impossibility of using the same species as a surrogate. This technology has triumphed only when using very closely related animals, with other cases including cloning of the coyote (Canis latrans) using domestic dog (Canis lupus familiaris) cells and surrogates (Hwang et al 2013), wild cat (Felis silvestris lybica) and sand cat (Felis margarita) using the domestic cat (Felis catus; G omez et al 2004,2008), and a mouflon (Ovis orientalis musimon), an endangered subspecies of sheep, using domestic sheep (Ovis aries) oocyte and surrogate following nucleus retrieval from a cell of a deceased mouflon (Loi et al 2001). It is clear, therefore, that deextinction by cloning using this technique is almost certainly achievable in theory.…”
Section: De-extinction Through Artificial Reproductive Technologiesmentioning
confidence: 99%
“…) and the coyote (Hwang et al . ), by using the oocytes from closely related species. It is commonly reported that the cloned animals are identical to their nuclear donors in genotypes and phenotypes, indicating the significant dominance of the nuclear genome in phenotypic determination.…”
Section: Introduction: Environmental Factors In Genetics and Developmentmentioning
confidence: 99%